Modeling of interregional migration based on an extended version of the Harris-Todaro - Bordoussov, O. V.; Ishuova, Zh. Sh. (Journal of Economic Research & Business Administration, 2016)
Interregional migration is one of the most important sources of formation of the population structure in the territory. Population migration is not just a territorial population movement with the intersection of internal and external administrative-territorial units, a complex social phenomenon, characterized by significant scale and diversity. The issue of analysis and modeling of migration is relevant for Kazakhstan due to significant territorial dimensions. The authors consider the inclusion in the model of migration of human capital, provision of public goods and housing. The main result is that the gross regional product per capita, unemployment and the distance between the regions have a significant impact on the strong migration of the population [8]. To analyze the determinants of migration in the regions of Kazakhstan according to the approach of Ghatak, Mulhern, Watson was expanded Harris-Todaro model by including variables that reflect the influence of human capital, housing and health care for migration flows.